PENGARUH JENIS KAYU DAN KOMPOSISI PEREKAT TAHAN CUACA TERHADAP SIFAT PAPAN PARTIKEL DUA JENIS KAYU HUTAN TANAMAN INDUSTRI - Suwandi Kliwon; M I lskandar; Paribotro Sutigno Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
This paper deals with an experiment on the effect of two timber estate wood species i.e. jeungjing (Albizia.falcataria Back), tusam (Pinus merkusii Yung et de Vries) and the composition of weather resistance resin (phenol formaldehyde) on the properties of particle board.All wood samples were obtained from West Java. The sample cut into 2 x 2 cm, 4 x 4 cm and 6 x 6 cm with 5 mm thick, respectively. Wood particles were glued with phenol formaldehyde resin. Particle board were made with 3 glue composition ( 10%, 12% and 14%) based on dry weight of wood particle and 3 wood particle dimension (0.5 mm x 20 mm x 20 mm, 0.5 mm x 40 mm x 40 mm and 0.5 mm x 60 mm x 60 mm).The properties of particle board were tested with Indonesia Industry Standard (SIl. 079783).The result indicated that: The physical and mechanical properties generally met Indonesian Standard. Analysis of variance for internal bond, shear strength and bending strength were significant different on wood species, particle size and the portion of phenol formaldehyde liquid resin. The portion of 14% phenol formaldehyde liquid resin based on the dry wood particle, its physical and mechanical properties were best, compared with others portion of phenol formaldehyde liquid resin (10% and 12%).